The Influence of Organizational Culture and Extrinsic Motivation on Employee Performance (A Study on The Regional Development Planning Agency of West Java Province) - Kurliyawati, Eli; Jusdijachlan, R.; Komar Priatna, Deden (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
One of the resources that the author focuses on is one of the functions of human resource management in the form of organizational culture and extrinsic motivation for the Performance of Civil Servants at the Regional Development Planning Agency of West Java Province. This is the focus of the author's observation on the grounds that the organization's resources, are one of the resources that are very closely related to other resources and activities carried out in the process of achieving organizational goals. One of the resources that the author focuses on is one of the functions of human resource management in the form of organizational culture and extrinsic motivation for the Performance of Civil Servants at the Regional Development Planning Agency of West Java Province. This is the focus of the author's observation on the grounds that the organization's resources, are one of the resources that are very closely related to other resources and activities carried out in the process of achieving organizational goals. In the preparation of this thesis, the author uses descriptive method research and quantitative approach. The samples taken in this study were 30 employees of Bappeda West Java Province. From the results of descriptive analysis, it is known that organizational culture is in the very good category, extrinsic motivation and performance are in the good category. Organizational culture and extrinsic motivation have an influence on the performance of employees of Bappeda West Java Province both partially and simultaneously.